Learning from mistakes climate scale: Development and validation - Lee, Michelle Chin Chin; Wo, Su Woan (Frontiers in Psychology, 2022)
Abstract Learning from mistakes plays an important role in employee development; however, such a learning scale has not yet been developed. The objective of this study was to develop and examine the psychometric properties of the Learning from Mistakes Climate Scale (LMCS) in Malaysia. A pool of items was first developed based on the literature, with an expert panel then convened to select items that met the definition of learning from mistake climate in the workplace, specifically in Malaysia. The experts agreed on 23 items to be rated. In total, 554 working adults with a mean age of 32.28 were then recruited for this study. The LMCS was administered at baseline and 10–14 days later as a retest: 468 participants took part in the retest study, a dropout rate of 15.52%. Confirmatory factor analysis showed that the LMCS is a 17-item one-factor model. Validity, in its various forms, was supported, namely, convergent validity, criterion validity, and predictive validity. Analysis also showed significant reliability, that is, test–retest reliability and in all intra-class correlations. The LMCS was found to be a valid and reliable instrument to assess the learning from mistake climate in Malaysia. This is the first scale in the organizational learning climate literature to integrate the mistake tolerance aspect. This instrument can assist in creating a psychologically safe work environment that helps to facilitate learning, especially in a highly hierarchical, collectivistic culture that is high in power distance. Keywords: scale development, validation, learning from mistakes climate, Malaysia, employee.